Copper-Catalyzed Cascade Synthesis of [1,2,4]-Triazoloquinazolinones - Lou, Zhenbang; Man, Ningning; Yang, Haijun; Zhu, Changjin; Fu, Hua (Synlett, 2018)
An efficient and practical method for the synthesis of 1,2,4-triazolo[5,1-b]quinazolin-9(3H)-ones has been developed via the copper-catalyzed domino reactions of readily available substituted N′-acetyl-2-bromobenzohydrazides with cyanamide. The protocol uses inexpensive CuI as the catalyst, and no other ligand or additive was required. The target products were prepared in good to excellent yields with tolerance of various functional groups.
Keywords: copper; domino reactions; [1,2,4]-triazoloquinazolinones; cyanamide; synthetic method